عبد القاهر الجرجاني و أفكاره في تحليل الأخطاء النحوية - Nuryani, Nuryani; Rohmat, Rohmat (Universitas Islam Negeri Sumatera Utara Medan, 2023)
The purpose of this study is to describe the types of grammatical errors made by students of the Arabic Language Study Program at Sayyid Ali Rahmatullah University, Tulungagung and correlate them with the views of Abdulqahir al-Jurjani. The methodology used is as follows: Type of research: This study is considered a qualitative descriptive study, the method used to find, analyze, understand, and comment on texts with Al-Jurjani's views, and (2) Data collection and analysis methods: This analysis has steps, namely: (1) collecting samples (academic theses) and Al-Jurjani's views related to the title; (2) identifying errors made by the sample; (3) clarifying the errors; (4) classifying the errors according to their causes and then commenting on Al-Jurjani's views. The results of this study are: (1) Abdulqahir al-Jurjani's views on grammar: grammatical and morphological rules ensure accuracy in sentence construction, and words in sentences influence each other; (2) Common grammatical errors in students' writing: first: grammatical errors in identifying the dependent and agent of a word or sentence; second: grammatical errors in identifying additional words. Third: Grammatical errors in determining the position of words in a sentence, which is useful for masculine, feminine, indefinite, and definite nouns. (3) Grammatical errors from Abdul-Qaher Al-Jurjani's perspective: Sentence structure and the relationship between words are very important. Words in a sentence influence each other through what are called